The Impact of Covid-19 Vaccines on Sperm Quality - Mujeeb-ur-Rehman Abro, Sania Pirzado, Barkat Ali Dahar, Khairunisa Shaikh, Masood Ahmed, Fozia Unar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the impact of Covid-19 vaccines on sperm quality. Study Design: Case control study Place and Duration of Study: Department of Diabetes & Endocrinology, Chandka Medical College Hospital Larkana from 1st July 2022 to 31st December 2022. Methodology: Patients were enrolled as 50 those who had PCR confirmed Covid 19 history and 50 those who never got Covid-19. On this basis those cases who had a Covid-19 history were placed in group A while those who did not had Covid-19 history were placed in Group B. Patients clinical history including anamnesis, marital status, cryptorchidism, operative varicocele, or any chronic ailment were documented. A counting chamber was used for sperm count in a 100 square area. Spermatozoa was measured as either rapid-progressively motile (Type a), or as slow-progressively-motile (Type b), or as situ motile (Type c), and finally as immobile (Type d). The total semen sperm count was gained by multiplication of concentration of sperm with its volume. Results: Volume and concentration was significantly different in both study groups. Difference in tail anomaly was also observed. In group A, it was 29.20 ± 10.26 while 27.59 ± 12.31 was the value of group B. Almost equal number of participants were married. Azoospermia was only found among Covid patients. Conclusion: Azoospermia was only found in Covid patients and no such results were obtained from Covid negative patients. Keywords: Spermatogenesis, Impairment, Corona virus, Congestion, Angiotensin